2016
DOI: 10.1080/02701960.2016.1144600
|View full text |Cite
|
Sign up to set email alerts
|

When I’m 64: Effects of an interdisciplinary gerontology course on first-year undergraduates’ perceptions of aging

Abstract: One challenge for gerontology is getting more students interested in aging at an earlier point in their academic career. This study evaluated the impact of an interdisciplinary course on aging designed for first-year undergraduate students. The course aimed to expand students’ appreciation of the personal and professional relevance of aging issues, with the goal of expanding their aging-related curricular and career interests. Main outcome variables of the study included knowledge of older adults and aging, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
(18 reference statements)
1
28
0
Order By: Relevance
“…For instance, it might be beneficial to introduce high school students to the field of aging by encouraging them to participate in community-based extracurricular programs that will allow them to work closely with older adults and aging professionals, or to partner with psychologists at local colleges or universities in aging-related science. At the college or university level, it is important to emphasize aging issues in specialized courses (Merz, Stark, Morrow-Howell, & Carpenter, 2016), but also to infuse that content within general courses in the curriculum (Lee & Waites, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…For instance, it might be beneficial to introduce high school students to the field of aging by encouraging them to participate in community-based extracurricular programs that will allow them to work closely with older adults and aging professionals, or to partner with psychologists at local colleges or universities in aging-related science. At the college or university level, it is important to emphasize aging issues in specialized courses (Merz, Stark, Morrow-Howell, & Carpenter, 2016), but also to infuse that content within general courses in the curriculum (Lee & Waites, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…A total of 670 individuals were analyzed in the seven studies included in this review. [22][23][24][25][26][27][28] Sample sizes in the individual studies ranged from 26 23 to 300 25 participants.…”
Section: Characteristics Of the Studies Selectedmentioning
confidence: 99%
“…A total of 438 participants were female. [22][23][24][25][26][27][28] The study conducted by Merz et al 28 presented the lowest mean age among participants (mean = 18.0 years; SD = 0.46), and the study by Nash et al 26 showed the highest mean age (mean = 35.1 years; SD = 7.4).…”
Section: Characteristics Of the Studies Selectedmentioning
confidence: 99%
See 2 more Smart Citations